ANALISIS PENDAPATAN PENGUSAHA KRUPUK HOME INDUSTRY UNTUK MENINGKATKAN EKONOMI PENGUSAHA DAN MASYARAKAT SEKITAR - aswat, muhamad chajar; Multifiah (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
This research was carried out in Balongsari Village, Ploso District, Jombang Regency. Primary data collected in the field for analysis purposes was obtained by observation, interviews and Documentation Studies, namely by directly visiting the place where Raya crackers are made, secondary data was obtained from literature studies and related agencies. is related to this research.The highest income contribution in the Raya cracker business is 44.2%, so it is in the category as a business branch, while the lowest income in the Raya cracker business with a contribution of 37.5% is in the category as a business branch.Keywords: Income analysis, home industry and cracker businesses.